Development and validation of high-performance liquid chromatography and high-performance thin-layer chromatography methods for the quantification of khellin in Ammi visnaga seed - Kamal, Abid (J Pharm Bioallied Sci, 2015)
OBJECTIVE: The present study was used to design simple, accurate and sensitive reversed phase-high-performance liquid chromatography RP-HPLC and high-performance thin-layer chromatography (HPTLC) methods for the development of quantification of khellin present in the seeds of Ammi visnaga. MATERIALS AND METHODS: RP-HPLC analysis was performed on a C18 column with methanol: Water (75: 25, v/v) as a mobile phase. The HPTLC method involved densitometric evaluation of khellin after resolving it on silica gel plate using ethyl acetate: Toluene: Formic acid (5.5:4.0:0.5, v/v/v) as a mobile phase. RESULTS: The developed HPLC and HPTLC methods were validated for precision (interday, intraday and intersystem), robustness and accuracy, limit of detection and limit of quantification. The relationship between the concentration of standard solutions and the peak response was linear in both HPLC and HPTLC methods with the concentration range of 10–80 μg/mL in HPLC and 25–1,000 ng/spot in HPTLC for khellin. The % relative standard deviation values for method precision was found to be 0.63–1.97%, 0.62–2.05% in HPLC and HPTLC for khellin respectively. Accuracy of the method was checked by recovery studies conducted at three different concentration levels and the average percentage recovery was found to be 100.53% in HPLC and 100.08% in HPTLC for khellin. CONCLUSIONS: The developed HPLC and HPTLC methods for the quantification of khellin were found simple, precise, specific, sensitive and accurate which can be used for routine analysis and quality control of A. visnaga and several formulations containing it as an ingredient.